INVENTORY FOR ASSESSMENT OF SOCIO-PERCEPTUAL ATTITUDE: PSYCHOMETRIC CHARACTERISTICS AND FEATURES OF USE - Tatiana D Dubovitskaya; Galina F Tulitbaeva; Alexander V Shashkov (Peoples' Friendship University of Russia (RUDN University), 2017)
Socio-perceptual attitude is defined as a predisposition of the subjects of communication to perceive, assess, and act in relation to each other in a certain way. The functions of social-perceptual attitudes are social adaptation (utilitarian function), cognitive function, expression and evaluation, and psychological protection. Author's technique of diagnostics of social-perceptual attitude of a person in relation to other people is presented in the article. The inventory uses the proverbs of the peoples of the world as test material. The results of psychometric testing indicate the reliability and validity of the technique.High scores on the technique results indicate the individual's characteristics such as willingness to trust, to help, and to notice positive experiences; the ability to see the positive potential; faith in people's ability to develop and achieve better results; emotional acceptance, benevolence, and empathy.The average scores indicate the subject's desire for close and trusting relationships, cooperation, sincerity; willingness to understand another person; desire to take into account individual psychological features of other people; contradictions with others are either absent or are resolved constructively.Low scores indicate that, in relation to others, the subject is characterized by the following: suspicion, anticipation of negative attitude to themselves, willingness to see the negative manifestations in the behavior of others, ignoring of their successes and achievements; emotional rejection, criticism, irony, malice; accusations against the others used to justify their own negative actions (aggression) against said others.The author's technique can be used in solution of the problem of psycho-diagnostics and therapy in order to optimize communication and interpersonal relations: achieve mutual understanding and cooperation, develop a constructive mutually beneficial solution, overcome the desire to criticize others.